Design and development of an IoT-based smart trolley with budget-limiting features to reduce queues in supermarkets - Zuchriadi, Achmad; Martana, Budhi; Rahayu, Fajar; Pradana, Sigit (Jurnal Mantik, 2025)
This study presents the design and implementation of a smart shopping trolley system based on Internet of Things (IoT) technology, aimed at improving retail efficiency and customer control. The system integrates an ESP32 microcontroller, RFID reader, LCD display, keypad, and buzzer to monitor total purchases in real time and alert users when a predefined budget is exceeded. Through a design and development methodology, the prototype was tested using 25 products and 10 scenarios. Results showed 100% accuracy in item detection and instant budget alert response. This research addresses a key gap in previous smart trolley systems by incorporating dynamic budget control and user-defined notifications. The system offers strong potential for further integration into real retail environments and serves as a foundation for future smart retail innovations.